Impact of mental disease on the risk of atrial fibrillation in patients with diabetes mellitus: a nationwide population-based study. (3rd October 2022) - Bae, N; Lee, S; Choi, E; Ahn, H; Ahn, H; Kwon, S; Han, K; Oh, S; Lip, G
Abstract: Background: Diabetes mellitus (DM) is known to increase the risk of mental disorders, which increases the health care burden in these patients. Also, DM is one of the risk factors leading to atrial fibrillation (AF), and the presence of concomitant AF and DM adds to the increased risks of stroke and death. It is uncertain whether mental disease is an independent risk factor of incident AF in patients with DM. Purpose: To investigate whether diabetic patients with mental disease have an increased risk of AF. Methods: Using the Korea National Health Insurance Service database, we enrolled 2, 512, 690 patients diagnosed with DM without AF between 2009 and 2021. Newly diagnosed AF was identified during the follow-up period. We compared the risk of AF between patients with mental disease and those without. Results: Among the total population, 828, 929 (32.99%; mean age 61.58±11.28; 56.71% female) patients were diagnosed with mental diseases (Figure 1). Anxiety (564, 786 patients, 68.13%) was the most common mental disease, while depression was the second most common (313, 773 patients, 37.85%). Diabetic patients with mental diseases had a higher percentage of women, hypertension, dyslipidemia, chronic kidney failure, congestive heart failure, obstructive sleep apnea, and thyroid disease. During a median 7.0 years (IQR 5.93–8.07) follow-up, 34, 523 were diagnosed new-onset AF (4.66 per 1, 000 person-year). In multivariate analysis, diabetic patients with mental disorders showed a higher risk of new-onset AF (HR 1.19; 95% CI 1.17–1.21; p-value <0.0001) (Figure 2). Among mental diseases, depression, insomnia, and anxiety were associated with increased risks of new-onset AF (HR 1.15; 95% CI 1.12–1.17; HR 1.15; 95% CI 1.13–1.18; and HR 1.19; 95% CI, 1.67–1.21; all p-value <0.0001, respectively), whereas bipolar disorder and schizophrenia showed non-statistically significant trends (due to small numbers). Subgroup analyses showed that younger age had significant interactions with depression, insomnia, and anxiety. Conclusion: Mental diseases, especially depression, insomnia, and anxiety, showed an increased risk of AF in patients with DM. Awareness and prompt diagnosis and management of AF would be necessary for these high-risk populations at risk of incident AF. Funding Acknowledgement: Type of funding sources: None.